2016
DOI: 10.1111/ijpo.12165
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial predictors and moderators of weight management programme outcomes in ethnically diverse obese youth

Abstract: Background An important area of research in childhood obesity is the identification of factors that predict or moderate the responses to obesity intervention programs, yet few studies have examined the impact of self-esteem and family functioning on obesity treatment outcomes. Objectives We sought to determine whether baseline self-esteem and family functioning predicted or moderated childhood obesity intervention outcomes at six months. Methods From 2009–2011, seventy-five 10–16 year old, racially/ethnica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 33 publications
(57 reference statements)
0
41
0
2
Order By: Relevance
“…Three studies did not report on personnel involved in intervention delivery. Parental involvement was reported as part of the intervention in 50 studies …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies did not report on personnel involved in intervention delivery. Parental involvement was reported as part of the intervention in 50 studies …”
Section: Resultsmentioning
confidence: 99%
“…The change in body image between pre‐intervention and postintervention was reported in 27 studies, between pre‐intervention and follow‐up in three studies, and 13 studies reported data at all three time points. Of the 40 studies reporting body image pre‐intervention and postintervention ranging in duration from 2 weeks to 24 months, body image was reported to be significantly improved compared with baseline in 22 studies, not significantly changed in 10 studies, five studies did not state whether or not the change was significant and three studies reported a significant improvement in one body image measure and no change in another.…”
Section: Resultsmentioning
confidence: 99%
“…Parenting is already a major component of FBT (eg, encouraging parents to offer praise and positive reinforcement for healthy energy‐balance behaviors). Although FBT is particularly beneficial (compared with standard care) for poorly functioning families, treatment could be tailored, when needed, to also educate parents on the importance of empathy, promoting child autonomy, and avoiding emotionally manipulative strategies for controlling their child's behavior. Finally, although weight‐control programs have been developed that focus on the social/peer aspects of food and activity behaviors, this content could be expanded to also focus on ways to improve children's subjective social status.…”
Section: Discussionmentioning
confidence: 99%
“…Pinhas‐Hamiel et al, showed no effect of age, yet did not include children below the age of 10, which may explain the different findings presented in our analysis. The reasons for the poorer response of pubertal adolescents to behavioral modification may range from the physiological effects of puberty to psychosocial factors . In addition, greater obesity duration, as expected in older adolescents, has been associated with an adverse metabolic profile and with modifications of the hypothalamus, both of which may impact the response to dietary interventions.…”
Section: Discussionmentioning
confidence: 99%